Characterization of chronic HCV infection in Northwest Spain: Impact of the treatment strategic plan of the Spanish National Health Service on HCV cure. Issue 7 (14th March 2017) - Grandal, Marta; Pernas, Berta; Mariño, Ana; Álvarez, Hortensia; Tabernilla, Andrés; Castro‐Iglesias, Ángeles; Mena, Álvaro; Delgado, Manuel; Pértega, Sonia; Poveda, Eva
Abstract : The aim of the study was to characterize HCV infection in Northwest Spain and assess the impact of the Spanish Strategic Plan to cure HCV infection. Overall, 387 patients were included (60.9% HIV/HCV coinfected and 28.2% cirrhotic). Of these, 72.9% of patients that were recognized as priority for HCV treatment according to the Spanish Strategic Plan (≥F2, transplant or extrahepatic manifestations), initiated treatment during 2015. Globally, SVR12 was achieved in 96.5% of patients. The implementation of the Spanish Strategic Plan has been critical to advance in HCV cure, but 27.1% of priority patients still remain awaiting HCV treatment initiation.